Factors affecting the income of Cassiavera farmers in Kerinci Regency - Nurhayani, Nurhayani; Haryadi, Haryadi; Zulfanetti, Zulfanetti (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2022)
Cassiavera's contribution to the regional economy of Kerinci Regency is 5.58%, 6.35% to the gross value added, and 21.23% the contribution to regional exports. Cassiavera's lands are mostly controlled by